Ecological security as a new challenge in local development - Rogowska-Sawicz, Małgorzata (Bezpieczeństwo ekologiczne jako nowe wyzwanie rozwoju lokalnego, 2025)
Aim: The aim of the article was to highlight the importance and increasing role of security (especially ecological security) in the implementation of local development policies, as well as to identify adaptive actions taken by local actors. Methodology: The research methods applied are of a descriptive and comparative nature, explaining the significance of security (ecological security) along with examples of adaptive actions. Results: Although the category of security, including ecological security, is not new in the literature, in the context of ongoing global processes (including climate change), it seems to be one of the most significant categories influencing how local development should be shaped by local entities. Implications and recommendations: Ongoing global changes reinforce the meaning of ecological security at different self-government levels. As a consequence increase the need to seek new solutions in terms of security and resilience for local governments. Originality/value: The article provides examples of solutions that can be implemented by local governments in the field of increasing ecological security.
Biblioteka Regionalisty = Regional Journal, 2025, Nr 25, s. 191-199
Keywords: local development; security; ecological security; rozwój lokalny; bezpieczeństwo; bezpieczeństwo ekologiczne